On Thermoeconomic Diagnosis of a Fouled Direct Expansion Coil: Effects of Induced Malfunctions on Quantitative Performance of the Diagnostic Technique - Antonio Piacentino; Pietro Catrini (Journal of Sustainable Development of Energy, Water and Environment Systems, 2017)

(untitled)
Thermoeconomic diagnosis represents a promising technique for the detection ofcommon faults in refrigeration systems, which are responsible of degradation in theirenergetic performance. Recently, the authors have carried out a sensitivity analysis of theperformance of this method to the thermodynamic conditions of inlet air and to thegeometry of the direct expansion coil, in case of degradation induced by evaporatorfouling. The analysis showed that the method is able to detect this fault, but sometimes itsquantitative assessments are not satisfactory. In order to understand more in-depth theorigin of such results and identify margins for refinement of the technique, this paper isaimed at evaluating at what extent changes in the exergetic performance of faults-freecomponents may negatively influence the model capability to detect the fouledevaporator and quantify the consequent additional exergy consumption. The resultssuggest that the method is particularly sensitive to the cost of “induced malfunctions” onthe compressor and the condenser, especially when low coil depth or high relativehumidity of inlet air are considered.